Pengaruh Sosial Media Marketing dan Gaya Hidup Terhadap Keputusan Pembelian di UMKM Mentai Malang - Rafif Nur Raekhan Gumay; Achmad Zaini; Fullchis Nurtjahjani (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
The number of internet users in Indonesia continues to grow every year, creating significant opportunities for Micro, Small, and Medium Enterprises (MSME) to utilize digital platforms as an effective marketing tool. One of the MSME that has successfully implemented this strategy is Mentai Malang. By utilizing the internet, Mentai Malang is able to reach wider market, to increase interaction with customers, and to strengthen brand awareness. Through social media platforms, Mentai Malang can communicate directly with customers, get input, and promote products efficiently and effectively. This research aims to examine the influence of social media marketing and lifestyle on purchasing decisions in Mentai Malang. This study used a quantitative approach. Data were obtained through observation and questionnaires. The sampling method used non-probability sampling which was purposive sampling technique with a sample size of 100 respondents. The results of the questionnaire were measured using a Likert scale. Data analysis used multiple linear regression with SPSS 25 for Windows. The results of partial and simultaneous hypothesis testing, social media marketing on purchasing decisions and lifestyle on purchasing decisions show that Social Media Marketing and Lifestyle have a positive and significant influence on purchasing decisions for Mentai Malang. Research shows that the Social Media Marketing variable has a greater contribution than Lifestyle. From the research results, it is concluded that Social Media Marketing and Lifestyle are one of the reasons why customers are satisfied with Mentai Malang MSME. A well-implemented Social Media Marketing strategy can increase purchasing decisions. In addition, the high lifestyle of the customer of Mentai Malang which is highlighted through promotion has a positive and significant impact on purchasing decisions.